Anaconda, Mont., Ordinances ch. 22, §§ 526-534 (1905) - (:unkn) unknown (My University, 1905)
Concealed Weapons: It shall be unlawful for any person within the limits of the City of Anaconda to carry or wear under his clothes or concealed about his person, any pistol, revolver, slung-shot, cross-knuckles, knuckles of lead, brass or other metal, bowie knife, dirk knife or dirk, razor or dagger, or any other dangerous or deadly weapon. Also provided licensure requirements and other information regarding concealed carry
Keywords: CARRY - CONCEALED